ACCOUNTING TREATMENT IN THE VILLAGE PUBLIC SECTOR: UNEXPECTED EXPENDITURES - Siswadi Sululing; Haliah Haliah; Andi Kusumawati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The current condition during the COVID-19 pandemic forces the Village Government to provide spending using unexpected expenditures in the Village Revenue and Expenditure Budget, which in normal conditions is rarely done. This study discusses the accounting treatment of unexpected expenditures conducted by the Village Government, which includes recognition, measurement, and presentation in financial statements. In this study, the researchers analyzed secondary data, namely the 2021 Village Revenue and Expenditure Budget Report using qualitative descriptive analysis to find out how the accounting treatment of unexpected expenditures was applied by the Village Government. The results of this study can be used as a reference by local governments in treating unexpected expenditures that have been realized during the COVID-19 pandemic. Keywords: accounting treatment, village public sector.